2020
DOI: 10.1039/d0ra01899f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV drug repurposing against SARS-CoV-2

Abstract: A novel severe acute respiratory syndrome human coronavirus (SARS HCoV) was identified from respiratory illness patients (named SARS-CoV-2 by ICTV) in December 2019 and has recently emerged as a serious threat to world public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 31 publications
0
72
0
1
Order By: Relevance
“… 240 In this case, ritonavir, lopinavir, and darunavir (anti-HIV drugs) were considered, and it was finally suggested that darunavir should be more selective for recognizing PLpro instead of 3CLpro. Nevertheless, additional docking studies suggest that darunavir could also be a suitable choice to bind 3CLpro, 241 , 242 highlighting the relevance of this particular anti-HIV drug as a potential anti-COVID-19 clinical drug.…”
Section: Sars-cov-2 Proteasesmentioning
confidence: 99%
“… 240 In this case, ritonavir, lopinavir, and darunavir (anti-HIV drugs) were considered, and it was finally suggested that darunavir should be more selective for recognizing PLpro instead of 3CLpro. Nevertheless, additional docking studies suggest that darunavir could also be a suitable choice to bind 3CLpro, 241 , 242 highlighting the relevance of this particular anti-HIV drug as a potential anti-COVID-19 clinical drug.…”
Section: Sars-cov-2 Proteasesmentioning
confidence: 99%
“…Furthermore, it has been recently reported that nelfinavir had anti-SARS-CoV-2 activity, as demonstrated in a cell-based experimental assay [12,13]. In addition, other HIV protease inhibitors such as indinavir, darunavir, and saquinavir, have been proposed as drug candidates against SARS-CoV-2 M pro , using computational studies [14][15][16][17][18]. These HIV protease inhibitors are repurposed drug candidates, some of which are already being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed comparison of the binding affinity among ligands, an estimation of the precise proteinligand complex structure is crucial and can be achieved by MD simulations with longer duration. Recently, several studies on promising inhibitors of M pro system, using molecular docking and MD simulations, have been reported[14][15][16][17][18]25,26]. These studies proposed several HIV-1 protease inhibitors as promising inhibitor candidates of M pro .…”
mentioning
confidence: 99%
“…To our knowledge, direct determination of the inhibition e cacy of HIV PIs against SARS-CoV-2 M pro in cell culture has not yet been attempted, although many in silico studies analyzing interaction between SARS-CoV-2 M pro and potential inhibitors were published [20][21][22][23][24][25][26] (Supplementary Table 1). Antiviral assays using lopinavir and ritonavir in Calu-3 cells were previously carried out for MERS-CoV, and the IC 50 for lopinavir, ritonavir and their combination was 11.6, 24.9, and 8.5 µM respectively [3].…”
Section: Discussionmentioning
confidence: 99%